Chronic pain effect on body schema and neuropsychological performance in athletes: a pilot study - Steca, P.; Norcini Pala, A.; Greco, A.; Monzani, D.; D'Addario, M. (Perceptual and Motor Skills, 2013)
The ability to recognize the body parts blindfolded is called body schema. Chronic pain disrupts cognitive function and could lead to an altered body schema. Commonly competitive athletes have chronic pain, but still train and compete. The goal of this study was to assess the body schema of competitive athletes with chronic pain. Pain was measured with the McGill Pain Questionnaire. To assess the body schema, the Image Marking Procedure was used to assess the capacity of the participants to project their bodies in space. Neuropsychological performance was assessed with the Grooved Pegboard Test. There was no difference in body schema between groups; neuropsychological performance indicated better scores in the athlete group. This study showed that despite chronic pain, the athlete group presented unaltered body schema and better neuropsychological performance, perhaps explained by self-selection.